Profitability and constraints to urban exotic vegetable production systems in the Kumasi metropolis of Ghana: A recipe for job creation - Camillus Abawiera Wongnaa; Margaret Atosina Akuriba; Amissah Ebenezer; Karen Sakyibea Danquah; Danso Anthony Ofosu (Journal of Global Entrepreneurship Research, 2019)
Some vegetable producers perceive their venture to be unprofitable owing to cheating at the farm gate. This study sought to determine profitability of production of exotic vegetables which are not native of Ghana. The study used data collected from 80 urban exotic vegetable farmers. Descriptive statistics, gross margin analysis, multiple linear regression, and the Garrett ranking scale were the methods of analysis. The most profitable system from the results of the net margin ratio was the production of lettuce as a sole crop with net margin ratio of 71% which explains the popularity of lettuce among exotic vegetable producers in the metropolis. Household size, experience, and access to credit positively affected profitability while farm size as well as costs of labor and fertilizer had negative effects. Farmers ranked high input cost, land tenure insecurity, and high cost of irrigation as challenges to urban exotic vegetable production. We recommend that urban exotic vegetable production should be considered as a source of employment. Government and financial institutions should improve farmer access to credit to enable them to hire adequate labor and acquire technologies and production inputs.
Keywords: 650; Cabbage; Cost; Ghana; Lettuce; Production systems; Revenue; Spring onion